A Quantitative Systems Physiology Model of Renal Function and Blood Pressure Regulation: Application in Salt‐Sensitive Hypertension. (27th May 2017) - Hallow, KM; Gebremichael, Y
Abstract : Salt‐sensitivity (SS) refers to changes in blood pressure in response to changes in sodium intake. SS individuals are at greater risk for developing kidney disease, and also respond differently to antihypertensive therapies compared to salt‐resistant (SR) individuals. In this study we used a systems pharmacology model of renal function (presented in a companion article) to evaluate the ability of proposed mechanisms to produce salt‐sensitivity. The model reproduced previously published data on renal functional changes in response to salt‐intake, and also predicted that glomerular pressure, a variable that is not easily evaluated clinically but is a key factor in renal injury, increases with salt intake in SS hypertension. We then used the model to generate mechanistic insight into the differential blood pressure and glomerular pressure responses to angiotensin converting enzyme (ACE) inhibitors, thiazide diuretics, and calcium channel blockers observed in SS and SR hypertension.